Inmigration, crisis and school - García Castaño, Francisco Javier; Olmos Alcaraz, Antonia; Ouafaa, Bouachra Outmani (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2015)
In recent years, it is common to find headlines in the Spanish Press saying, «employment has dwindled due to the crisis and the lack of jobs has forced immigrants to return to their natives homes…» Added to these headlines, assertions such as «immigrants are no longer coming» can be found. These statements have been used to justify the gradual reduction of the services provided to this population. At the school level, similar voices are being heard,supporting the reduction of educational aids alleging that «immigrants are not coming» or «they have left». In this paper, we have attempted to evaluate this set of allegations that relate the «economic crisis» to «the return» of the population of foreign nationality. For that purpose, three major issues will be addressed. Firstly, the evolution of the foreign population attending the Spanish school system will be analysed. Secondly, the Statistics on Migrations and the Municipal Register of Inhabitants will be used to examine the issues related to the immigrants’ return. Finally, we will reflect on how the notion of«return» of the foreign population is being used in order to reduce theresources that are provided to them in the educational system.
Keywords: immigration; crisis; return; school; Spain